Strawberry (Fragaria × ananassa cv. Romina) methanolic extract attenuates Alzheimer's beta amyloid production and oxidative stress by SKN-1/NRF and DAF-16/FOXO mediated mechanisms in C. elegans. (15th March 2022) - Navarro-Hortal, María D.; Romero-Márquez, Jose M.; Esteban-Muñoz, Adelaida; Sánchez-González, Cristina; Rivas-García, Lorenzo; Llopis, Juan; Cianciosi, Danila; Giampieri, Francesca; Sumalla-Cano, Sandra; Battino, Maurizio; Quiles, José L.
Graphical abstract: Highlight: Strawberry methanolic extract was rich in phenolic compounds and minerals. Treatments significantly delayed amyloid β-protein induced paralysis in CL4176. The extract reduced oxidative stress induced by AAPH in the wild strain. Effects were mediated by DAF-16 and SKN-1 pathway signaling. Strawberry could be an excellent ingredient to be used for functional food. Abstract: Bioactive compounds from strawberries have been associated with multiple healthy benefits. The present study aimed to assess chemical characterization of a methanolic extract of the Romina strawberry variety in terms of antioxidant capacity, polyphenols profile and chemical elements content. Additionally, potential toxicity, the effect on amyloid-β production and oxidative stress of the extract was in vivo evaluated in the experimental model Caenorhabditis elegans . Results revealed an important content in phenolic compounds (mainly ellagic acid and pelargonidin-3-glucoside) and minerals (K, Mg, P and Ca). The treatment with 100, 500 or 1000 μg/mL of strawberry extract did not show toxicity. On the contrary, the extract was able to delay amyloid β-protein induced paralysis, reduced amyloid-β aggregation and prevented oxidative stress. The potential molecular mechanisms present behind the observed results explored by RNAi technology revealed that DAF-16/FOXO and SKN-1/NRF2 signaling pathways were, at least partially, involved.